Methods of mechanical grinding and dispersion analysis of solids; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Inozemtsev S. V. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана